Visible Light Effects on Photostrictive/Magnetostrictive PMN‐PT/Ni Heterostructure (Adv. Mater. Interfaces 36/2022). Issue 36 (20th December 2022) - Dagur, Deepak; Polewczyk, Vincent; Petrov, Aleksandr Yu.; Carrara, Pietro; Brioschi, Marta; Fiori, Sara; Cucini, Riccardo; Rossi, Giorgio; Panaccione, Giancarlo; Torelli, Piero; Vinai, Giovanni
Abstract : Multiferroic Heterostructures In article number 2201337, Piero Torelli and colleagues demonstrate that by illuminating a PMN‐PT/Ni multiferroic heterostructure with low power visible light, the magnetic properties of the magnetostrictive Ni layer are influenced by the light‐induced modifications of the photostrictive ferroelectric substrate, as proved spectroscopically via x‐ray magnetic circular dichroism.